Retrospective Analysis of COVID-19 Vaccination in a University Hospital and the Relationship with the Epidemic Rate - Işıl Deniz Alıravcı; Fatma Gümüşer; Alper Şener (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2022)
It was aimed to make a retrospective analysis of the vaccines administered in the vaccine unit of our hospital since the beginning of the COVID-19 pandemic. The study was carried out retrospectively from the vaccination records our hospital, 14 January 2021 to 01 July 2022. In the 18-month period, a total of 75079 (100%) vaccines were administered, 59386 (79%) were Biontech and 15693 (21%) were Sinovac vaccines. Only Sinovac was available until June, therefore, 66% of the Sinovac vaccines were administered in the first five months period. After the Biontech vaccine started to be applied in our hospital, the rates of Sinovac vaccination have declined drastically.  When the epidemic and vaccination graphs were examined separately, inverse correlation was found between the peak points of the epidemic and vaccine graphics. Biontech was found to be the most preferred vaccine by individuals against COVID-19 in this study.